Os investimentos públicos na economia sergipana : uma análise das despesas orçamentárias de 2000 a 2007 - Gonçalves, Bruno Setton (2009)
The concern with the effect of the public expenses in the economy is recurrent, over all with the impacts of them on the economic growth with this the society waits always an efficient allocation of the public resources, since limits for the expansion of the prescriptions exist that finance the increase of the expenses per capita. This only strengthens the necessity of increase of the productivity of the public expenses. In end the objective of this study is to analyze theoretician and empirically the effect of the public expenses in the sergipana economy in the period of 2000 the 2007, over all the impacts of the investments in infrastructure on the economic growth of the State, of form added, catching the liquid rocking of the participation of the expenses on the internal product.